What are the odds? Identifying factors related to competitive success in powerlifting - Daniel J. van den Hoek; Patrick J. Owen; Joel M. Garrett; Robert J. Howells; Joshua Pearson; Jemima G. Spathis; Christopher Latella (BMC Sports Science, Medicine and Rehabilitation, 2022)
Abstract Background The ability for athletes to gain a competitive advantage over their opponents is well recognised. At times, this advantage may be considered a marginal gain. However, in the context of competition, marginal advantages may be the difference between winning and losing. This investigation explores how competition factors influence the odds of competitive success (i.e. winning) in powerlifting (PL) to assist athletes and coaches in achieving a competitive advantage. Methods A cross-sectional, retrospective analysis of competition data from raw/classic, Australian powerlifting competitions 2010–2019 was conducted. Data included 10,599 competition entries (males: n = 6567 [62%], females: n = 4032 [38%]). Independent t-tests were used to compare continuous data between sexes or winners and non-winners at an event. Cohen’s d and the 95% confidence interval (d [95% CI]) were calculated. Univariate odds of winning an event based on independent variables (age [irrespective of category], sex, body weight and weight of first lift attempt [regardless of success]), were assessed by separate simple logistic regression. Results When compared to males, the odds of winning for females were 50% greater (OR [95% CI] 1.500 [1.384, 1.625]; P < 0.001). Athletes who had larger first lift attempts (Squat: + 7.0 kg P < 0.001, Bench Press: + 3.2 kg P < 0.001, and Deadlift: + 6.1 kg P < 0.001and competed for a longer period (winners: 401 vs non-winners: 304 days, P < 0.001) had an increased likelihood winning. Age was associated with increased odds of success for males (OR [95% CI] 1.014 [1.009, 1.019], P < 0.001) per additional year of age for males, but not females (P = 0.509). Conclusions Multiple factors appear to contribute to the likelihood of winning a PL competition. These results may help coaches to develop competition and training strategies that optimise athletes’ likelihood of competitive success in PL.